(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines single-member sentences as the most important part of syntax, in which units of all levels of language intersect and integrate. Comparative linguistics is one of the most important areas of modern linguistics. The material for the study was proverbs, riddles and texts selected from works of art by Russian and Uzbek authors.